Painting as Process : Re-evaluating Painting. - Tag, Eugene; Nyen, Ho Tzu; Sagerman, Robert; Nadarajan, Gunalan; Earl Lu Gallery, LASALLE-SIA College of the Arts, Singapore (Singapore : Lasalle-Sia College of Arts, 2004)
Begg, Torie ; de la Cruz, Angela ; Davenport, Ian ; Harding, Alexis ; Nyen, Ho Tzu ; Martin, Jason ; Richter, Gergard ; Sagerman, Robert ; Tai Si, Yong
Earl Lu Gallery, LASALLA-SIA College of the Arts, Singapore, 5 June - 4 July 2004
kunstcatalogus